YOSHLARNI HARBIY-VATANPARVARLIK RUHIDA TARBIYALASHDA JISMONIY TARBIYA VA SPORTNING O‘RNI - Eshbekov, S.J.; Arziev, Sh.A. (SCIENCE and SOCIETY, 2023)
The purpose of this article is that the role of physical education and sports in educating young people in the spirit of military patriotism is incomparable, and that educating young people in the spirit of military patriotism is a duty to the motherland and the content of the sense of belonging to the motherland, harmonizing the interests of each person with the interests of the country. It is a creative idea that urges him to serve the people's happiness.as one of the directions of military-patriotic education, it is a component of the activities carried out to prepare the young generation to achieve high results in physical education and sports in various spheres of life, including the performance of important social functions in the defense of the homeland.it is highlighted that military patriotism is considered as one of the priority tasks of state policy.
Keywords: homeland; in sports; military; neighborhood; devotion; love; education; values; young people; patriotism; heroes; loyalty